Impact of visual presentation of atherosclerotic carotid plaque on cardiovascular risk profile using mHealth technologies - Greta Ullrich; Alexander Bäuerle; Lisa Maria Jahre; Katrin Paldán; Jana Rosemeyer; Chiara Kalaitzidis; Christos Rammos; Martin Teufel; Tienush Rassaf; Julia Lortz (npj Digital Medicine)
Abstract This randomized, controlled trial evaluated the impact of plaque visualization combined with daily tasks on cardiovascular risk profile and included 240 participants with coronary arterial disease. The intervention group received the PreventiPlaque app during the 12-month study period in addition to standard care. The app contained daily tasks that promoted lifestyle modifications and adherence to prescribed medication. It included ultrasound images of participants´ individual carotid plaque, which were updated regularly. The impact of plaque visualization and personalized app usage was evaluated, using a change in the SCORE2 as a primary endpoint. In the intervention group, the SCORE2 was significantly lower after the study period (t(120) = 6.43, p adj < 0.001, d RM = 0.58). This demonstrates the efficacy of the PreventiPlaque app in supporting lifestyle modifications and medication adherence. These findings suggest that personalized mHealth interventions in combination with visual risk communication are valuable tools in secondary prevention. Trial Registration: The study was registered at ClinicalTrials.gov under the identifier NCT05096637 on 27 October 2021 and was approved by the local ethics committee of the University of Duisburg-Essen (20-9157-BO).